2021
DOI: 10.1073/pnas.2100198118
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of rotavirus RNA chaperone displacement and RNA annealing

Abstract: Rotavirus genomes are distributed between 11 distinct RNA molecules, all of which must be selectively copackaged during virus assembly. This likely occurs through sequence-specific RNA interactions facilitated by the RNA chaperone NSP2. Here, we report that NSP2 autoregulates its chaperone activity through its C-terminal region (CTR) that promotes RNA–RNA interactions by limiting its helix-unwinding activity. Unexpectedly, structural proteomics data revealed that the CTR does not directly interact with RNA, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 72 publications
(114 reference statements)
2
30
0
Order By: Relevance
“…However, this region of the NTS is not resolved well enough to highlight direct contacts. Contacts between this Cas10d patch and the NTS likely stabilize the nascent R-loop at early stages of TS:NTS duplex melting and thus favor R-loop completion via kinetic partitioning 9 , 38 , 39 . While this patch of positively charged residues is somewhat analogous to the K-vise and K-rim found in type I-E and I-F Cascade complexes 17 , 33 , we observe a different path for the NTS in type I-D Cascade.…”
Section: Resultsmentioning
confidence: 99%
“…However, this region of the NTS is not resolved well enough to highlight direct contacts. Contacts between this Cas10d patch and the NTS likely stabilize the nascent R-loop at early stages of TS:NTS duplex melting and thus favor R-loop completion via kinetic partitioning 9 , 38 , 39 . While this patch of positively charged residues is somewhat analogous to the K-vise and K-rim found in type I-E and I-F Cascade complexes 17 , 33 , we observe a different path for the NTS in type I-D Cascade.…”
Section: Resultsmentioning
confidence: 99%
“…To move towards a better understanding of phase separation of viroplasm‐forming proteins NSP5 and NSP2, and to directly demonstrate their capacity to drive LLPS, we analysed their propensities to undergo LLPS in vitro . Previously, N‐terminal and C‐terminal tagging of NSP5 had been shown to affect formation of viroplasm‐like inclusions (Fabbretti et al , 1999), while C‐terminal His‐tagging of NSP2 does not affect their assembly (preprint: Bravo et al , 2020). We therefore examined recombinantly expressed untagged NSP5 (Fig EV2) and a C‐terminally His‐tagged NSP2 (cHis‐NSP2, see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Given that viroplasms are viewed as sites of viral replication (Silvestri et al , 2004; Patton et al , 2006) that accumulate rotavirus transcripts where they may be remodelled by the RNA chaperone NSP2 (Borodavka et al , 2017; Bravo et al , 2018; preprint: Bravo et al, 2020), we examined how solubilisation of NSP5/NSP2 condensates would affect their RNA composition in vivo . smFISH analysis of the RV genomic segment 3 (Seg3) and segment 4 (Seg4) transcripts in MA104‐NSP5‐EGFP cells confirmed that viroplasms contained both RNAs at 4 HPI (Fig 6A, left ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, DNA dissociation from DrmA(∆loop)B bound DNA was not observed. Furthermore, a second super-shift occurred at protein concentrations of 1µM or higher, likely corresponding to multiple copies of the complex binding to the DNA concurrently, as observed for other nucleoprotein complexes 26,27 .…”
Section: Drma Contains An Unstructured Trigger Loop That Partially Occludes the Dna-binding Sitementioning
confidence: 67%